2022
DOI: 10.3389/fenvs.2022.1074992
|View full text |Cite|
|
Sign up to set email alerts
|

Can digital financial inclusion help reduce agricultural non-point source pollution?—An empirical analysis from China

Abstract: In the context of financial support for rural revitalization, digital financial inclusion may become a new “gospel” to alleviate agricultural surface source pollution. Based on the panel data of 30 Chinese provinces from 2011 to 2020, the study constructs a fixed-effects model to test the mitigation effect of digital financial inclusion on agricultural non-point source pollution empirically. The study finds that: 1) Digital financial inclusion has a mitigating effect on agricultural non-point source pollution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Therefore, the excessive use of pesticides, chemical fertilizers, and agricultural plastic films has resulted in increasingly severe ANSP. Secondly, the influencing factors of ANSP were studied (Yi et al, 2021;Lin et al, 2022;Duan and Li, 2023;Wang et al, 2023). Agricultural mechanization and the use of agrochemicals have contributed to the exponential growth of agricultural production and agricultural waste in many countries and exacerbated ANSP (Yi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the excessive use of pesticides, chemical fertilizers, and agricultural plastic films has resulted in increasingly severe ANSP. Secondly, the influencing factors of ANSP were studied (Yi et al, 2021;Lin et al, 2022;Duan and Li, 2023;Wang et al, 2023). Agricultural mechanization and the use of agrochemicals have contributed to the exponential growth of agricultural production and agricultural waste in many countries and exacerbated ANSP (Yi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agricultural mechanization and the use of agrochemicals have contributed to the exponential growth of agricultural production and agricultural waste in many countries and exacerbated ANSP (Yi et al, 2021). The level of environmental regulation and the level of digital financial development can also mitigate ANSP (Lin et al, 2022). The adjustment of the internal structure of the agricultural industry will change the form and intensity of agricultural pollutant emissions (Wang et al, 2023), which in turn will have a particular impact on ANSP.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the high-quality development of agriculture in the border regions may be impacted differently by various stages of the development of digital inclusive finance. Different effects are caused by high quality development [7] . Considering this, proposes hypothesis 2: Hypothesis 2: The influence of digital inclusive finance on the high-quality growth of agriculture in China's border regions has a threshold effect.…”
Section: A Theoretical Examination Of the Threshold Effect Of Inclusi...mentioning
confidence: 99%
“…Based on these, Jiang et al (2020) established a panel-smoothed transformation regression model and concluded that the increase in ANSP due to agricultural economic growth is largely related to the level of financial development and that increasing the level of finance to a medium-high threshold will suppress ANSP (Jiang et al, 2020). Lin et al (2022) empirically tested the mitigation effect of digital financial inclusion on ANSP by constructing a fixed-effects model based on provincial data in China. Some scholars have also found that with the improvement of the development level of digital inclusive finance, the effect of pollution mitigation is enhanced (Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%